ARTHOUSE CINEMA ON THE FUTURE OF SOUTH KOREA: KIM KI DUK - E. A. Ostrovskaya (Концепт: философия, религия, культура, 2018)
Analyzing different segments of modern Korean cinema it may be affirmed that its relevant topics are the following: religious ideologies, ideological choice, value orientations of individual life and biography. Within the frame of the Korean history, it becomes obvious that an authentic cultural and religious self-reflection is a major ideological trend of modern South Korean society. This is also true for the films created by South Korean film directors popular in the West. Among them is Kim Ki Duk, whose works focus on the reflections about South Korean Modernity. This article deals with his film "Spring, Summer, Autumn, Winter... and Spring" (2003), devoted to the comprehension of the role of traditional ideology in constructing the life project of a modern man. The author of the article proposes the detailed discourse analysis, revealing the key discourse, key ideologemes and the director's central message. According to the author's conclusion, the nodal discourse is devoted to the consideration of Buddhism as a traditional religious culture and world outlook framework for Korean culture. According to Kim Ki Duke's central message, the modern Korean society ought to search for Weltanschauung in its historical religious tradition, which is presented by Buddhism. One can always return to it, and its resource is able to provide support in a situation of desperation and choice.